Perceptions and Experiences of Continuity of Care (COC) Nurses in Lower Limb Fracture Patients: Phenomenological Approach - Akbar Nur; Masfuri; Setyowati; Achmad Fauzi Kamal; Trevino Aristarkus Pakasi (Universitas STRADA Indonesia, 2025)
Background: Traffic accidents remain a major public health concern globally, particularly in developing countries like Indonesia, which ranks among the highest in road traffic-related mortality. Indonesia, as one of the fourth most populous countries in the world, is at greater risk for increased mortality from traffic accidents. Lower limb fractures are frequently associated with considerable morbidity and lengthy hospital stays. Purpose: This study identifies the perceptions and experiences of continuity of care (COC) nurses in lower limb fracture patients. Methods: This research utilizes a descriptive qualitative model with a phenomenology approach. Researchers recruited respondents after obtaining ethical clearance and an approval letter from West Sulawesi Provincial Hospital. In this study, 5 participants were determined according to the inclusion criteria set by the researcher. The data collection process was carried out by conducting a Focus group Discussion (FGD) for 40–60 minutes. During the FGD, the researchers used FGD notes and field notes. The analysis in this study used content analysis. Results: This study explored nurses' perceptions and experiences of continuity of care (COC) fracture patients in the lower extremity. This study identified four themes, namely, continuity of care (COC) in fracture patients, perceived physical discomfort, support needs in ambulating, and support for improving nurse competency. Conclusion: The implementation of COC can be a solution to the physical discomfort experienced by patients. Nurse support, family support, interprofessional support, and hospital support are needed so that COC can be implemented properly to improve musculoskeletal recovery and sustainable independence in lower limb fracture patients. The hope of the participants, in addition to motivation and the availability of tools for ambulation exercises, should be provided in the surgical room, especially in the treatment room for patients with musculoskeletal system disorders.